Mode Choice Analysis between Executive Rail and Sleeper Bus on the Surabaya – Jakarta Corridor Using Binary Logit Regression - Slamet Wahyudi; Hera Widyastuti (Newinera Publisher, 2026)
Surabaya and Jakarta are two major cities in Indonesia that serve as national centers of business, economic activity, and government administration, resulting in high intercity mobility between them. The operation of the Trans‑Java Toll Road has accelerated the growth of sleeper bus services, while executive rail remains a preferred mode due to its stable comfort and reliability. This study aims to identify passenger characteristics, analyze the probability of mode choice based on factors such as fare affordability, travel time, comfort, calmness, and safety, and propose service improvements for both modes. A revealed preference survey was conducted with two hundred respondents who had already selected either executive rail or sleeper bus for their Surabaya–Jakarta trip. The data were analyzed using binary logistic regression to model the probability of choosing each mode. The results show that most passengers belong to the choice‑user category at 65.5 percent and are predominantly private‑sector employees at 52.5 percent. The key determinant for selecting executive rail is the importance placed on calmness and comfort, yielding a predicted probability of 78.52 percent. In contrast, the dominant factor influencing sleeper bus selection is safety consideration, with a predicted probability of 96.52 percent. These findings indicate that executive rail attracts passengers seeking a quiet and comfortable travel environment, while sleeper buses appeal to travelers prioritizing safety and time efficiency supported by toll‑road connectivity. The study concludes that service improvements should focus on enhancing comfort and safety to strengthen the attractiveness of both premium land transport modes along the Surabaya–Jakarta corridor.